Pakikisama in the Context of Wives’ Lived Realities in Post-Marital Residence with In-Laws - Roy Basas; Princess Izy Calinisan; Ericka Cauguiran; John Patrick Datingaling; Christian Tejeresas; Rachel Anne Bernardino (RSF Press, 2026)
This qualitative study explored the lived experiences of seven Filipino wives residing with their in-laws in multigenerational households through in-depth, semi-structured interviews analyzed using Interpretative Phenomenological Analysis (IPA). Analysis followed iterative IPA procedures (initial noting, emergent theme development, and cross-case synthesis) supported by QDA Miner Lite, with analytic rigor ensured through researcher reflexivity, memo writing, and sustained engagement with the data. Guided by Family Systems Theory, Family Conflict Theory, Transformative Learning Theory, and the Filipino cultural construct of pakikisama, the study examined how emotional, relational, and cultural conditions shaped wives’ everyday realities. Eight interrelated themes emerged: (1) Relational Burnout, the depletion of personal resources from daily household life; (2) Emotional Exhaustion, fatigue from sustained relational demands; (3) Multidimensional Support, moral, emotional, and financial assistance from in-laws often experienced as obligatory; (4) Identity Tension, challenges in negotiating personal roles within the household; (5) Harmonious Restraint, deliberate emotional regulation and strategic silence to maintain peace; (6) Persistent Living Arrangement, long-term co-residence as a structural and emotional reality difficult to change; (7) Transformative Adaptation, increased self-awareness and personal growth through prolonged cohabitation; and (8) Mandated Pakikisama, the cultural imperative to uphold harmony and respect (paggalang). Findings portray Filipino wives as active negotiators of gendered emotional labor, sustaining family cohesion within extended households. By foregrounding pakikisama as both a cultural resource and constraint, the study extends qualitative literature on multigenerational households and gendered emotional labor beyond Western-centric frameworks, challenging assumptions that emotional labor is invisible or secondary and demonstrating how it is culturally mandated and relationally embedded in non-Western contexts, with implications for culturally responsive family support systems.